Rota Turística e Gastronômica Santa Maria - Silveira Martins: o desenvolvimento do turismo na Quarta Colônia de imigração italiana - Stecker, Débora Tessle (2010)
Ahead of the importance of the preservation and valuation of the patrimony, it is distinguished Tourist and Gastronomic Route Santa Maria - Silveira Martins, projected enters the agricultural and urban way them two cities that congregate different patrimonies in its trajectory. The Route, to be servant, took in consideration basic the historical and cultural elements for the ambient construction of the regional identity, characteristics, religious and the gastronomies, as well as a planning as for the form of management conceived for the regional development, from the Tourism. In this direction, tourism, regional development and cultural patrimony of this central region of the Rio Grande Do Sul, known as pertaining to the Fourth Colony of Italian Immigration, are valued and integrated in this project that created the Tourist Gastronomic Route.